Distributed Management as a Solution of the “Goal-Tool” Principle of Economic Policy - O. S. Sukharev (Управленческие науки, 2021)
The study subject is the process of substantiation and implementation of measures of the state economic policy aimed at achieving the established priority goals of economic development from the standpoint of the “goal-tool” principle and its possible expansion. The purpose of the research is to substantiate the doctrine of so-called distributed management, which expands the use of the principle of “goal-tool” in relation to the developed and implemented economic policy, as well as to identify the main advantages, disadvantages, opportunities for its use for the public administration methods development. The content of the named doctrine comes down to identifying the structure of tools that affect the management object with a different and changing force, according to which the introduction of these tools is planned. The methodological basis was formed by the theory of management of large-scale systems, the economic policy of Tinbergen, the method of comparative analysis, and the formalization of the management process. The result boils down to identifying a significant advantage of distributed management for the formation of economic policy, since it allows to identify their correlation with the development factors, including an assessment of the strength of the applied instruments. This expands on the classic “goal-tool” principle of economic policy. Distributed management allows you to give a qualitative assessment of the institutional coordination of economic activities by the government. The use of distributed control will be most appropriate when deploying indicative planning procedures and constituting the content of the project management method, which involves the selection of a set of tools from alternative options. In the future, distributed management makes it possible to identify errors in copying managerial and organizational experience in terms of the applied development institutions, borrowed technologies, and the use of project management. A quantitative assessment of the strength of tools and its sensitivity of various goals, the application of this assessment to specific controllable systems of different levels of complexity constitutes the prospect of this theoretical study.